PENGARUH CURRENT RATIO DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURN OVER TERHADAP RETURN ON ASSETS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pudjut Harianto, Rudy; Maisyarah, Putri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This research aims to analyze the influence of Current Ratio, Debt to Equity Ratio and Total Assets Turn Over on Return on Assets in registered food and beverage companies on the Indonesian Stock Exchange period of 2016-2022. Data Analyse method that used in this research are Multiple Linier Regression Analyse (correlation coeficient, determination coeficient, simultaneous test/F test, and partial test/t test). Accumulatively, coeficient correlation (R)= 0,636 so that it can be said that the independent variables toward dependent variable in this research can giving the strength correlation. Result of determination coefficient (R2)= 0,371 it can be said the independent variables can be explain the dependent variable of equal to 37,1% only. While the rest equal to 62,9% explained by other variable from outside model. The result of significantion test could be explained:(1) Current Ratio has no effect in a positive direction and is not significant on the Return On Assets;(2) Debt to Equity Ratio has a negative and significant effect on the Return On Assets; and (3) Total Asset Turn Over does not have a negative effect and is not significant on the Return On Assets. The result of simultaneous test could be explained: variables of Current Ratio, Debt to Equity Ratio, and Total Assets Turn Over simultaneously have effect and significant on the Return On Assets variable.